Nootropic activity of butanolic extract Passiflora ncarnata leaves - Suvarna Ingale; Sanjay Kasture (International Journal of Phytomedicine, 2012)
Alzheimer’s disease (AD) is the most common cause of dementia among people of age 65 and older. Nootropics are a class of psychotropic drugs that enhance learning, acquisition and reverse learning impairments in experimental animals. Numerous plants have been used to treat cognitive disorders in the traditional medicine. Passiflora incarnata Linn (Family: Passifloraceae) has been widely used in traditional medicine as sedative, anxiolytic, antispasmodic, analgesic, anticonvulsant, and wormicidal. Till date there are no reports on nootropic activity of Passiflora incarnata. Hence, in the present study, nootropic activity of n-butanol extract of P. incarnata leaves (BEPI) was studied using elevated plus maze and object recognition test. The results of the study signified that n-butanol extract of P. incarnata leaves containing flavonoids possessed nootropic activity indicated by shortening of transfer latency (TL) and an increase in discrimination index. Pretreatment with BEPI protected the animals from memory deficits produced by scopolamine. The results of present study confirmed that nootropic effect of BEPI is mediated through facilitation of brain cholinergic neurotransmission and major phytoconstituent like flavonoids, alkaloids and phenolic compounds may be responsible for nootropic effect of P. incarnata